Safeguarding Ukraine’s Cultural Heritage in War: Identifying the Obligations of Non-Parties to the Conflict, with Special Focus on the European Union - Jakubowski, Andrzej (Polish Review of International and European Law, 2024)
Russia’s aggression against Ukraine is a true war against cultural heritage. However, while international law regulates the obligations and duties of parties to an armed con"ict, the eective protection of cultural heritage largely depends on the conduct of non-participants. Hence this article addresses the nature and content of the legal obligations to protect Ukraine’s cultural heritage incumbent on non-parties to the con"ict. Its main focus is on the European Union (EU) due to its close political, legal, economic and cultural ties with Ukraine. It explains that cultural considerations today permeate almost all EU policies. In addition, Member States and the Union itself are bound by a number of international law obligations in relation to cultural heritage and cultural rights. This article further demonstrates that such obligations increasingly address the protection of heritage as a common good of all humankind, linked to the maintenance of global peace and security, and to the protection and promotion of all human rights. While referring to the EU’s current practice in safeguarding Ukraine’s heritage, this article envisages and advocates further developments in this respect.